The CFTR K464N variant in fetuses potential increases premature birth risk in Chinese families - Jingping Li; Lingyun Zhang; Fangfang Xi; Chuanping Lin; Qitao Zhan; Qing Zhou; Shi Zheng; Weikang Chen; Fan Jin (Human Genomics)
Abstract Background Global fertility decline has led to increased use of assisted reproductive technology (ART), raising concerns about genetic risks to offspring. This study aimed to investigate cystic fibrosis transmembrane conductance regulator (CFTR) variants in Chinese families and assess their association with pregnancy complications and neonatal outcomes. Methods This prospective cohort study included 446 Chinese families (148 natural conceptions, 298 ART conceptions) who underwent whole genome sequencing. We analyzed the frequency of pathogenic/likely pathogenic CFTR variants and their association with preterm birth (PTB), pregnancy complications, and neonatal outcomes. Results Twelve pathogenic/likely pathogenic CFTR variants were identified, with K464N (c.1392G > T) being the most prevalent (2.9% of cohort). PTB incidence was significantly higher in pregnancies with fetal CFTR variants (43.1%, 22/51) compared to those without (17.5%, 69/395; p < 0.001). Fetuses carrying the CFTR K464N variant exhibited a 3.39-fold increased risk of PTB (95% confidence interval (CI): 1.39–8.23, p = 0.007) after adjusting for confounders. Neither fetal nor maternal CFTR variants were significantly associated with other neonatal outcomes, including neonatal weight, Apgar scores, respiratory distress, or hyperbilirubinemia (p > 0.050). Conclusion These findings suggest a potential association between fetal CFTR K464N variant and increased risk of preterm birth in Chinese families, highlighting the importance of considering CFTR genotyping in prenatal care.